2020
DOI: 10.1515/gps-2020-0022
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis and characterization of carboxymethyl guar gum: Application in textile printing technology

Abstract: AbstractThis study focusses on the synthesis of carboxymethyl guar gum (CMG) via monochloroacetic acid under alkaline conditions. The reaction conditions were also optimized during the course of experiment. Guar derivative with variable degree of substitution (DS) were prepared and were confirmed by Fourier transform infrared (FTIR) spectroscopy. The DS was determined quantitatively by titration method for each derivative. The synthesized guar gum derivatives, being the natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The degree of O ‐carboxymethyl substitution was calculated following the methods reported earlier. [ 22,33,34 ] Briefly, the sodium form of carboxymethyl gum was converted to hydrogen form and then the hydrogen form of the gum was dissolved in standardized sodium hydroxide solution. The solution was then back titrated with standardized HCl to a phenolphthalein end‐point.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of O ‐carboxymethyl substitution was calculated following the methods reported earlier. [ 22,33,34 ] Briefly, the sodium form of carboxymethyl gum was converted to hydrogen form and then the hydrogen form of the gum was dissolved in standardized sodium hydroxide solution. The solution was then back titrated with standardized HCl to a phenolphthalein end‐point.…”
Section: Methodsmentioning
confidence: 99%
“…Commercial alginate thickener was comparable in terms of penetration, fixing ability, and colour fastness. These first findings revealed that GG might be employed as a green, not dangerous, cost‐effective, and environmentally friendly thickener in textile printing 17 …”
Section: Introductionmentioning
confidence: 93%
“…It is grown from the grains of yearly leguminous plants that thrive in India, Pakistan, Iran, and also the southern United States 11 . As a result, guar and its derivatives have a wide range of commercial and industrial applications in water treatment, 12,13 drug delivery system (DDS), 14,15 solar cells 16 and textiles 9,17,18 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations